Cinque canti = Five cantos - Ariosto, Lodovico, 1474-1533 (Biblioteca italiana., 1996)
This new translation brings to English-speaking readers an intense and brooding work by the greatest poet of the Italian Renaissance, Ludovico Ariosto. Begun as a sequel to his epic masterpiece, Orlando Furioso (1516), the unfinished Cinque Canti are a powerful poem in their own right. Tragic in tone, they depict the disintegration of the chivalric world of Charlemagne and his knights and give poetic expression to a sense of cultural, political, and religious crisis felt in Ariosto's Italy and in early sixteenth-century Europe generally. David Quint's introduction freshly examines the literary sources and models of the Cinque Canti and discusses the cultural contexts and historical occasions of the poem. Printed with facing Italian text, this volume allows the modern English reader to experience a work of Renaissance literature whose savage beauty still has the power to chill and fascinate.